Regulation of Combining Brokerage Activities in the Securities Market in the Legislation of the EAEU Countries - KANATOV, Renat K. (Journal of Advanced Research in Law and Economics, 2019)
This research is devoted to the analysis of legal norms on combining brokerage activities in the securities market with other types of entrepreneurial activity in the countries of the Eurasian Economic Union. Recently, consideration of issues of harmonization of the legislation of the countries of the Eurasian Economic Union has gained particular importance in conditions of ensuring freedom of movement of goods, services, capital and labor, pursuing a coordinated, consistent or uniform policy in economic sectors within the framework of the Eurasian Economic Union; the formation of a single market for goods, services, capital and labor  within the Eurasian Economic Union; creation of conditions for stable development of the economies of the countries of the Eurasian Economic Union in the interests of improving the living standards of their population; comprehensive modernization, cooperation and competitiveness of national economies in the global economic space. In this regard, the aim of the article is to identify problems and develop provisions for harmonizing the legislation of the countries of the Eurasian Economic Union in terms of combining brokerage with other types of professional activities in the securities market in the countries of the Eurasian Economic Union. The results of the study in this article can be used in law-making to harmonize the legislation of the countries of the Eurasian Economic Union in the field of regulation of brokerage in the securities market, as well as in scientific research in the field of civil and business law.